Green orchid bee Euglossa dilemma Friese (Insecta: Hymenoptera: Apidae) - Aaron Mullins (EDIS)
Green orchid bees are a quite conspicuous and charismatic species. This is mostly due to their large size and bright metallic-green coloration. They are very fast and agile flyers, and can be seen quickly darting from flower to flower separated by long periods of hovering. Male orchid bees collect fragrant volatile compounds from their environment and present them to females by fanning their wings and “spray ventilating” their bouquet for the inspection of prospective mates. In Florida, male green orchid bees are attracted to chemicals produced by certain wood-rot fungi, decomposing vegetation, perfume flowers, and certain essential oils such as clove and cinnamon oil. Male green orchid bees can be quickly and easily attracted and observed by soaking a small piece of paper with clove oil and placing it outside. This 4-page fact sheet was written by Aaron Mullins, and published by the UF Department of Entomology and Nematology, October 2013. http://edis.ifas.ufl.edu/in1013